Candidiasis and demodicosis of facial skin imitating exacerbation of rosacea - Anna Łańczak; Maciej Spałek; Honorata Kubisiak-Rzepczyk; Dorota Jenerowicz; Monika Bowszyc-Dmochowska; Zygmunt Adamski (Termedia Publishing House, 2019)
Rosacea is a chronic dermatosis, manifesting with erythema, papular or pustular eruptions located in the facial area. The authors present a case of an 84-year-old woman with a long-term history of rosacea who had a mycotic infection of the facial skin imitating aggravation of the underlying disease. The case presented by us can be regarded as a variant of "tinea incognito", i.e., undiagnosed mycosis, misdiagnosed as another dermatosis, which is often aggravated by the patient by using local glucocorticosteroids or other local immunomodulators, which hinders proper diagnosis. It may be diagnostically relevant to consider other comorbidities in elderly patients with rosacea.